Maternal isolated hypothyroxinemia in the first trimester is not associated with adverse pregnancy outcomes, except for macrosomia: a prospective cohort study in China - Du, Jing; Ji, Linong; Zhang, Xiaomei; Yuan, Ning; Sun, Jianbin; Zhao, Dan (Frontiers in Endocrinology, 2023)
Objective: Insufficient thyroid hormone levels during pregnancy, especially in the first trimester, adversely affect maternal and fetal health. However, the impact of isolated hypothyroxinemia (IH) on adverse pregnancy outcomes remains controversial. Therefore, this study aimed to investigate the association between IH during the first trimester and adverse pregnancy outcomes. Methods: This prospective cohort study included 1236 pregnant women. Thyroid-stimulating hormone and free thyroxine levels were measured before 13 weeks of gestation. Logistic regression analysis and the Cochran-Armitage trend test were used to assess the association between IH in the first trimester and adverse pregnancy outcomes. Results: IH during the first trimester was associated with an increased risk of macrosomia. After adjusting for confounding factors, including age, body mass index, parity, abnormal pregnancy history, fasting blood glucose, and total cholesterol, multivariate logistic regression analysis showed that IH in the first trimester remained an independent risk factor for macrosomia. In addition, the risk of macrosomia increased with IH severity. However, no significant relationship was found between IH during the first trimester and gestational diabetes mellitus, hypertensive disorders of pregnancy, spontaneous abortion, premature rupture of membranes, placental abruption, oligohydramnios, premature delivery, fetal distress, or low birth weight. Conclusion: IH during the first trimester did not increase the risk of adverse pregnancy outcomes, except for macrosomia.